P–568 Homozygous Pathogenic Variants in ACTL9 Cause Fertilization Failure and Male Infertility in Human and Mouse. (6th August 2021) - Dai, J; Zhang, T; Guo, J; Zhou, Q; Gu, Y; Zhang, J; Hu, L; Zong, Y; Song, J; Zhang, S; Dai, C; Gong, F; et al.
Abstract: Study question: What are the other male factors that cause total fertilization failure (TFF) excepting for variants in PLCZ1? Summary answer: Homozygous variants in ACTL9 (actin like 9) cause abnormal localization of PLCζ in a loosened perinuclear theca (PT) structure and leads to TFF. What is known already: In previous studies, investigators have reported that the female factors in TFF after intracytoplasmic sperm injection (ICSI) include pathogenic variants in WEE2, TLE6, and TUBB8, whereas for male factors, pathogenic variants in PLCZ1 were reported to be the primary cause of TFF, which account for approximately 30% of couples with male factors in TFF excluding globozoospermia. Most recently, it was reported that pathogenic variants in ACTL7A led to reduced expression and abnormal localization of PLCζ, thereby identifying this genetic variant as a potential cause of TFF. Study design, size, duration: Fifty-four infertile couples with TFF or poor fertilization (fertilization rate of < 20%) at the Reproductive and Genetic Hospital of CITIC-Xiangya during January 2014 to June 2020 were recruited into this study. Participants/materials, setting, methods: Male factors were identified in (MOAT). WES analysis was used to analyze the genetic factors of individuals with male factors. Sperm morphological study was conducted by H&E staining and TEM. Immunostaining of PLCζ was used to analyze the status of sperm-borne activation factor. A knock-in mouse model was generated by CRISPER-Cas9 technology. Sperm from homozygous Actl9 variant mice were analyzed by TEM and ICSI. ICSI with AOA was performed in couples with ACTL9 variants. Main results and the role of chance: A total of 54 couples with TFF or poor fertilization were screened, with 21 couples determined to have a male infertility factor by MOAT. Whole-exome sequencing of these 21 male individuals identified three homozygous pathogenic variants in ACTL9 in three individuals. ACTL9 variations led to abnormal ultrastructure of the PT, with PLCζ absent in the head and present in the neck of the mutant sperm, which contributed to failed normal calcium oscillations in oocytes and subsequent TFF. The key roles of ACTL9 in the PT structure and TFF after ICSI were further confirmed in Actl9-mutated mouse model. Furthermore, assisted oocyte activation by calcium ionophore exposure successfully overcame TFF and achieved live births in a couple with an ACTL9 variant. Limitations, reasons for caution: The mechanism of how ACTL9 regulate PLCζ remains unknown. Wider implications of the findings: It provided a genetic marker and a therapeutic option for individuals who have undergone ICSI without successful fertilization. Trial registration number: not applioable